Exposición académica, preparación y conducción de la exposición - Villaorduña Peña, Ovedt Lincoln (2018)
The purpose of education is to form people capable of achieving their ethical, intellectual, artistic, cultural, physical, spiritual and religious fulfillment, promoting the formation and consolidation of their identity and self-esteem and their adequate and critical integration into society. With respect to the area of Communication, in Regular Basic Education, the aim is for students to develop communication skills to interact with other people in different contexts and circumstances, in addition to understanding and building reality, and representing the world in a real or imaginary way. The student interprets reality and makes decisions based on the knowledge he or she has learned through experience. The learning that the area of Communication provides contributes to understanding the contemporary world, making decisions and acting ethically in different areas of life. Therefore, through this session we will develop the structure for a good planning and conduction of academic exposure, which will be useful for students to develop their communication skills to a given audience so that it can be prepared for any competition that society demands.